Re-imagining cultural studies : the promise of cultural materialism - Milner, Andrew (London ; Thousand Oaks, Calif. : Sage, 2002)
Re-imagining Cultural Studies restores Williams to a central position in relation to the formation and development of cultural studies. The book is a much-needed reappraisal of the Williams approach, correcting misinterpretations and demonstrating its singular relevance to the problems and potentials facing cultural studies today.
Cover; Contents; Acknowledgements; Chapter 1 -- Cultural Materialism and Cultural Theory; Chapter 2 -- Politics and Letters; Chapter 3 -- From Culture to Society; Chapter 4 -- Theorising Culture; Chapter 5 -- Rethinking Mass Civilization; Chapter 6 -- Rethinking Minority Culture; Chapter 7 -- Towards 2050; Bibliography; Index.
Includes bibliographical references (pages 182-197) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Williams, Raymond -- Political and social views; Williams, Raymond; Social evolution; Historical materialism; Culture; Cultural Evolution; Évolution sociale; Matérialisme historique; SOCIAL SCIENCE -- Anthropology -- Cultural; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Popular Culture; Culture; Historical materialism; Political and social views; Social evolution; Kulturtheorie; Kulturwissenschaften; Cultuurfilosofie; Culturele studies; Marxisme; Cultural studies -- Philosophie; Kulturtheorie; Kulturwissenschaften